Methodology for consideration of system quality within manufacturing - Foehr, Matthias (2014)
The present paper deals with the question how system quality can be influenced within its engineering and manufacturing. It focuses on discrete manufacturing by system of systems and presents a methodology to gather and analyze relevant influences on system quality within a MPFQ-model. The model is based on four main elements: Materials, Processes, Functions and Quality. The paper brings together functional design/thinking in system of systems engineering with system engineering and manufacturing design. It will show the basic architecture behind the MPFQ model and how quality influences can be methodically detected. Afterwards the application of the MPFQ-model will be shown and benefits will be evaluated.